Kajian Pelaksanaan Operasional dan Pemeliharaan Sarana Air Bersih di Desa Citalang Kabupaten Purwakarta - Zaenab Arifah Syamsurizal; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2022)
Proper practice of operations and maintenance of water supply system is necessary to ensure the fulfillment of community’s water need while maintaining the continuity of functionality of the water facility. This study aims to explore the practice of operations and maintenance of water facilities in Citalang Village. Data collection is done through deep interviews with operator and beneficiaries of four water facilities in Citalang Village and field observation. This study uses qualitative approach with inductive analysis, referring to the analysis of Miles and Huberman model and Spradley model. Result of the finding shows a degree of how operations and maintenance of water facility conducted in four different locations. The implementation of technical procedures is important to achieve the proper practice of water facility operations, while maintenance need to be carried out through routine and periodic inspection and restoration. Evidence also suggests several factors that hamper the potential sustainability of the water supply system, namely the absence of routine maintenance mechanism and the absence of tariff structure supporting it, the absence of operator rotation, the absence of collective agreement on efficient water consumption, and finally financial limitations of beneficiaries.